Inferior Vena Cava Mesenchymal Tumor with Intracardiac Extension Mimicking an Atrial Myxoma in a Young Adult: A Case Report - Maia, Laura Maria Esper Peixoto; Maia, Filipe Peixoto (Brazilian Journal of Case Reports, 2026)
Mesenchymal tumors originating from the inferior vena cava with cranial extension into the right atrium are rare and may closely mimic primary cardiac tumors, particularly atrial myxoma, leading to diagnostic and surgical pitfalls. A 29-year-old previously healthy man was referred for cardiac surgery after a large right atrial mass was detected by transthoracic echocardiography and interpreted as an atrial myxoma. No preoperative cross-sectional imaging was performed. Intraoperatively, the lesion was identified as cranial extension of a tumor arising from the inferior vena cava, prompting partial intracardiac resection. Subsequent magnetic resonance imaging demonstrated a large infiltrative right retroperitoneal mass with extensive inferior vena cava tumor thrombosis. The patient underwent definitive staged multidisciplinary surgery including retroperitoneal tumor resection, inferior vena cava tumor thrombectomy, and caval reconstruction with a vascular graft. Histopathology demonstrated a smooth muscle neoplasm with cellular atypia, diffuse smooth muscle marker expression, Ki-67 labeling index of approximately 15%, and p53 positivity, without tumor necrosis or mitotic activity, supporting classification as a tumor of uncertain malignant potential. This case highlights the critical importance of systematic inferior vena cava assessment in patients presenting with right atrial masses, as misdiagnosis may lead to inadequate surgical planning and increased perioperative risk. It also illustrates the diagnostic complexity of vascular smooth muscle tumors with atypical features and underscores the need for complete surgical resection, long-term anticoagulation with rivaroxaban after caval reconstruction, and structured oncologic surveillance in tumors of uncertain malignant potential.